Model and Strategy of Dynamic Collaborative Governance of Poverty Alleviation In West Java - Triantoro, Arvian; Rahayu, Agus; Adi Wibowo, Lili; Disman, D; Arief Ramdhany, Muhamad; Hardiana, R. Dian (Jurnal ASET (Akuntansi Riset), 2024)
The purpose of this study is to examine the description of the collaboration environment, collaborative dynamic-capability, and dynamic-collaborative governance, and analyze the effect of collaboration environment on collaborative dynamic-capability and dynamic-collaborative governance of poverty alleviation in West Java. The approach is quantitative, with questionnaires as the main instrument for collecting and analyzing datasets to describe each variable in the model and its interrelationships, tested with Partial Least Squares Structural Equation Modeling (PLS-SEM). The research subjects or units of analysis in this study are all 27 cities/regencies in West Java, plus one provincial government as respondents. The results revealed that collaboration environment and collaboration environment had a positive effect on collaborative dynamic capability. The collaborative dynamic capability had a positive effect on dynamic-collaborative governance. The amount of regional generated revenue for local governments was able to moderate the relationship among variables. This study offers practical implications for enhancing poverty alleviation strategies through targeted collaborative governance frameworks. It highlights the importance of fostering dynamic capabilities and effective local government. This study highlights the novelty of integrating dynamic governance with moderated revenue-based insights.